Application of Wetland-Based Entrepreneurship Orientation and Entrepreneurial Competence to Increase MSME Income in Wetlands - Anisah, Hastin Umi; Isnawati; Rifqi Novriyandana; Muchammad Yusup (HM Publisher, 2021)
This study aims to determine and analyze the application of wetland-based entrepreneurial orientation and entrepreneurial competence to increase MSME income. With the increase in the income of MSMEs, it is expected to improve the welfare of MSMEs. Quantitative research method used in this research with PLS analysis technique. As for the long term, MSME actors, in this case